2012
DOI: 10.1007/s00253-012-4209-7
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic antimicrobial silver nanoparticles produced by fungi

Abstract: Aspergillus tubingensis and Bionectria ochroleuca showed excellent extracellular ability to synthesize silver nanoparticles (Ag NP), spherical in shape and 35 ± 10 nm in size. Ag NP were characterized by transmission electron microscopy, X-ray diffraction analysis, and photon correlation spectroscopy for particle size and zeta potential. Proteins present in the fungal filtrate and in Ag NP dispersion were analyzed by electrophoresis (sodium dodecyl sulfate polyacrylamide gel electrophoresis). Ag NP showed pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 25 publications
4
36
0
9
Order By: Relevance
“…Biological route synthesis of nanoparticles has received much focused attention from researchers in order to elucidate the mechanism of synthesis. To circumvent this many biological systems like bacteria [Kumar CG et al, 2011], fungi [Rodriques AG et al, 2012], yeast, cyanobacteria, actinomycetes and plants have been used. But the best one appears to be the use of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Biological route synthesis of nanoparticles has received much focused attention from researchers in order to elucidate the mechanism of synthesis. To circumvent this many biological systems like bacteria [Kumar CG et al, 2011], fungi [Rodriques AG et al, 2012], yeast, cyanobacteria, actinomycetes and plants have been used. But the best one appears to be the use of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Both mycogenerated particles were spherical with the sizes between 25 nm and 45 nm. These fungal AgNPs showed to be highly effective against human pathogen Candida sp., frequently occurring in hospital infections [136].…”
Section: Figure 10mentioning
confidence: 99%
“…al. [136] from the Mangrove plant and their cell-free media used to synthesise AgNPs. While nanoparticles were produced rapidly by both fungi, Bionectria ochroleucaI produced medium was more efficient than that of Aspergillus tubingensis.…”
Section: Figure 10mentioning
confidence: 99%
“…9,10 Nanoparticles biosynthesized by organisms, without involving the toxic solvents, strict conditions, or expensive processes that are needed in chemical methods, have become a popular subject. 11 Various nanoparticles are reported that are biosynthesized by bacteria, [12][13][14] fungi, 15,16 plants, 17,18 mammalian cells, 19 or even earthworms. 20 Considering the simple culture methods, the low cost of the equipment, and the easy way to get the gradients, the biosynthesis of nanoparticles using microorganisms is the most economic and common approach.…”
Section: Open Access Full Text Articlementioning
confidence: 99%